2014
DOI: 10.1016/j.tetlet.2014.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of novel fluorinated subnaphthalocyanines for organic photovoltaic cells

Abstract: Novel fluorinated subnaphthalocyanine derivatives were newly designed and synthesized as donor materials for low molecular organic photovoltaic cells using fullerene as an acceptor. They were designed to have the low-lying HOMO energy levels for improvement of open circuit voltage without any expense of short-circuit current density. The HOMO/LUMO energy levels of hexafluoro-, heptafluoro-, dodecafluoro-, tridecafluoro-and the parent subnaphthalocyanine estimated based on the photoelectron spectroscopy were-5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Takao et al also treated the two products with AgBF 4 to substitute the axial chloride with a uoride. 20 In addition to the synthesis of 'standard' BsubNcs from 2,3-dicyanonaphthalene, Kobayashi et al also prepared chiral analogs of BsubNcs via the reaction of 1,2-dicyanonaphthalene with BCl 3 to form chiral Cl-1,2-BsubNc and subsequent phenoxy derivatives. 21 A review of the above mentioned studies (see Table S1 †) reveals that detailed characterization of the BsubNcs is generally limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takao et al also treated the two products with AgBF 4 to substitute the axial chloride with a uoride. 20 In addition to the synthesis of 'standard' BsubNcs from 2,3-dicyanonaphthalene, Kobayashi et al also prepared chiral analogs of BsubNcs via the reaction of 1,2-dicyanonaphthalene with BCl 3 to form chiral Cl-1,2-BsubNc and subsequent phenoxy derivatives. 21 A review of the above mentioned studies (see Table S1 †) reveals that detailed characterization of the BsubNcs is generally limited.…”
Section: Introductionmentioning
confidence: 99%
“…1 H and 19 F NMR data are reported (both numerically and graphically) along with HRMS data by Takao et al (entry 6). 20 BsubPcs have recently been applied as functional materials in organic electronic devices most notably in organic photovoltaic devices (OPVs). [22][23][24][25][26][27][28][29][30][31] Although the recent efforts of our group 29,30 and others [25][26][27][28]31 have shown that a variety of BsubPcs can have application in OPVs, the majority of the applications have focused on the use of the prototypical derivative Cl-BsubPc.…”
Section: Introductionmentioning
confidence: 99%
“…The voltage generated by the organic photovoltaic cell, VOC, is related to the energy gap between the HOMO energy level of the donor and the LUMO energy level of the acceptor materials [21,22], so that control of the HOMO/LUMO energy levels of the electron donors and acceptors is important to optimize the performance of OPVs. We also reported that the HOMO/LUMO energy levels of organic active layers can be controlled by introducing appropriate polar substituents to fullerenes [23] and subphthalocyanines [24].…”
Section: Introductionmentioning
confidence: 96%
“…Chlorosubphthalocyanines possess a peculiar conical structure, which provides them with relatively high solubility and low tendency for aggregation [4]. These subphthalocyanines have been utilized in many fields such as organic photovoltaics (OPV) [5,6], chemical sensors [7], organic light-emitting diodes (OLEDs) [8], organic thin film transistors (OTFTs) [9], supramolecular building blocks for molecular cages [10], solar cells [11,12] and non-linear optics [13].…”
Section: Introductionmentioning
confidence: 99%